A young woman with steroid‐responsive, IgG4‐positive plasma cell‐enriched cystic lymphangioma and chylous ascites. Issue 6 (17th April 2018) - Al Zaki, Alaa A.; Mann, Shawna L.; Carruthers, Mollie N.; Slack, Graham W.; Chen, Luke Y. C.
Key Clinical Message: Lymphangiomas are benign tumors of the lymphatic vessels, which can be inflammatory and occasionally steroid‐responsive. IgG4‐related disease (IgG4‐RD) is a recently defined fibro‐inflammatory condition. We describe a novel association between reactive IgG4+ plasma cells and cystic lymphangioma in a young woman who had a dramatic clinical response to steroids. Abstract : Lymphangiomas are benign tumors of the lymphatic vessels, which can be inflammatory and occasionally steroid‐responsive. IgG4‐related disease (IgG4‐RD) is a recently defined fibro‐inflammatory condition. We describe a novel association between reactive IgG4+ plasma cells and cystic lymphangioma in a young woman who had a dramatic clinical response to steroids.